Contribution of major economies to global GDP and product reallocation around the world - Maria Llop (Heliyon, 2024)
Economic globalization has led to production increasingly becoming concentrated in certain regions and countries of the world. This article develops an accounting framework to provide the trends for the contribution of countries to global gross domestic production (GDP). In particular, the method transforms the multiregional input-output model to quantify the relative importance of individual economies to world GDP. The proposal uses a world input-output database that distinguishes between three main economic areas: China, the United States of America and the European Union. The results suggest that identical changes in sectoral demand asymmetrically modify the relative contributions from individual economies, with China showing the highest positive (negative) impact after an increase (decrease) in world demand. These findings suggest that a generalized economic expansion (contraction) is linked to a boost (decline) in the asymmetries of production across the world.